2009
DOI: 10.3945/ajcn.2008.26829
|View full text |Cite
|
Sign up to set email alerts
|

Association between n-3 fatty acid consumption and ventricular ectopy after myocardial infarction

Abstract: These findings extend existing evidence linking n-3 fatty acid consumption to a reduced risk of ventricular arrhythmias by showing that a greater intake of n-3 fatty acids may be associated with low ventricular ectopy among AMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
(53 reference statements)
0
15
0
1
Order By: Relevance
“…Indeed, the Physician's Health Study reported a 52% reduction in the risk of sudden death in subjects who ingested fish at least once per week but no reduction in the risk for myocardial infarction (Albert et al, 1998. The incidence of ventricular arrhythmias was inversely related to dietary n−3 PUFAs; an effect that remained even after other cardiovascular comorbidities were controlled (Smith et al, 2009). An even more striking association between n−3 PUFA consumption and reduced risk for sudden death has been reported in studies in which blood n−3 PUFA levels were determined (Siscovick et al, 1995;Albert et al, 2002;Pottala et al, 2010;Aarsetoey et al, 2011); the subjects with the highest n−3 PUFA blood levels exhibited a 70% to 90% reduction in the risk for sudden cardiac death .…”
Section: Epidemiological Studiesmentioning
confidence: 96%
“…Indeed, the Physician's Health Study reported a 52% reduction in the risk of sudden death in subjects who ingested fish at least once per week but no reduction in the risk for myocardial infarction (Albert et al, 1998. The incidence of ventricular arrhythmias was inversely related to dietary n−3 PUFAs; an effect that remained even after other cardiovascular comorbidities were controlled (Smith et al, 2009). An even more striking association between n−3 PUFA consumption and reduced risk for sudden death has been reported in studies in which blood n−3 PUFA levels were determined (Siscovick et al, 1995;Albert et al, 2002;Pottala et al, 2010;Aarsetoey et al, 2011); the subjects with the highest n−3 PUFA blood levels exhibited a 70% to 90% reduction in the risk for sudden cardiac death .…”
Section: Epidemiological Studiesmentioning
confidence: 96%
“…And if such a mechanism of omega-3 fatty acids exists, perhaps an earlier intervention when life-threatening arrhythmias ensue would be best. Despite evidence that links n-3 fatty acid consumption before hospitalization to a reduced risk of ventricular arrhythmias among AMI patients, 18 evidence to document a benefit of omega-3 supplementation within the first several days after an infarct is lacking.…”
Section: Article See P 2152mentioning
confidence: 99%
“…Further evidence indicate that total fat, saturated fat and trans fat can enhance inflammation and visceral obesity resulting in to MS and treatment with w-3 fatty acids may be beneficial [40][41][42]. In a recent study, a total of 117 volunteers completed the 12-week trial.…”
Section: Risk Factorsmentioning
confidence: 99%